Mobile Banking: Drives Changes in The Consumptive Behavior of Generation Z in Batu Ampar Kramat Jati - Fadillah, Putri Nur; Subali, Subali (BASKARA : Journal of Business and Entrepreneurship, 2024)
AbstractThe rapid development of technology has led to various changes in the banking industry, including the rise of electronic payments such as mobile banking. This study aims to understand the impact of mobile banking on the consumption behavior of Generation Z in the Batu Ampar area of Kramat Jati. The study collected quantitative data through questionnaires distributed to 100 respondents with sampling techniques, namely non-probability sampling in the form of purposive sampling. The data was then analyzed using the SPSS 25 (Statistical Package for the Social Sciences) application. The results showed that there is a significant relationship between mobile banking and consumptive behavior. The regression test revealed that for every 1% increase in mobile banking usage, the value of consumption behavior increases by 1.471. Through the Product Moment Correlation Analysis, it is known that R count 0.05 ≥ 0.000 means that there is a significant relationship between Mobile Banking (X) and Consumptive Behavior (Y). In the F test, it is obtained that F count is 36.417 F table, namely 3.94, which can be seen that variable X (Mobile Banking) has an effect on variable Y (Consumptive Behavior) which means Hα is accepted and H0 is rejected by having an influence value of 27.1% of the consumption behavior can be attributed to mobile banking, while the remaining 72.9% is influenced by other factors not considered in this study. Overall, these findings highlight the influence of mobile banking on the consumption behavior of Generation Z.